STRATEGI PENGURANGAN PENGGUNAAN KANTONG PLASTIK DI KABUPATEN BANYUWANGI; STUDI PADA SURAT EDARAN BUPATI BANYUWANGI NOMOR: 660/412/429.104/2019 - Yuniar, Nabila Yuniar; Rahayu, Sri Rahayu; Priyanto, Hary Priyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas 17 Agustus 1945 Banyuwangi, 2024)
Use of plastic bags in modern life looks very fast, causing a higher level of human dependence on plastic. This is due to the fact that plastic is a practical wrapper or container that looks clean, easy to get, durable, and is also cheap. In Banyuwangi, in terms of policies to reduce the use of plastic bags is BWI MEDATIK (Banyuwangi Merdeka of Plastic). But in this case, there are still many people who use plastic bags. That is due to the lack of equitable socialization, carried out by the DLH government (Department of the Environment) so that the presence of plastic is still circulating in Banyuwangi District. This research uses descriptive qualitative method, using observation data collection techniques, guided free interviews, and documentation. In conducting strategies to reduce the use of plastic offices, researchers used the POAC approach, namely: planning, organizing, actuating, and controlling, and using the SWOT approach, namely: strengths, weaknesses, opportunities, and threats. The results of the study are that the government does not provide evenly disseminated information about reducing the use of plastic bags to all communities in Banyuwangi District, so that many people still use plastic bags. That is because, the government has not issued an absolute policy on reducing the use of plastic bags, so the use of plastic bags is considered trivial by the people in Banyuwangi District.